Lifecycle duration and maturity heterogeneity of jatropha curcas linn - Jupikely James Silip; Armansyah H. Tambunan; Herliza Hambali; Sutrisno Anggoro; Memen Surahman (Canadian Center of Science and Education, 2010)
Jatropha is new oilseed crop and little is known about its reproductive characters. Therefore this study was conducted with the main objective to determine the lifecycle duration of Jatropha fruits from seeding to appearance of buds, fruit set, physiologically matured, ripening and senescence. To obtain more information on the fruit maturity, fruit maturity uniformity in seven local jatropha accessions was studied. During the study it was observed that Jatropha start to bear a flower after 90 to 120 days of seeding. The study also showed a wide variation in days to physiologically maturity of fruit, ripening and senescence. This crop showed indeterminate characteristics with fruits maturing at the bottom of the stem while buds developed at the top of the plants. Results of this study demonstrate that Jatropha is an indeterminate crop, which requires careful harvest and postharvest handling to increase harvestable fruits and therefore could reduce harvesting cost.